2004
DOI: 10.1084/jem.20041135
|View full text |Cite
|
Sign up to set email alerts
|

Important Roles for E Protein Binding Sites within the Immunoglobulin κ Chain Intronic Enhancer in Activating Vκ Jκ Rearrangement

Abstract: The immunoglobulin κ light chain intronic enhancer (iEκ) activates κ rearrangement and is required to maintain the earlier or more efficient rearrangement of κ versus lambda (λ). To understand the mechanism of how iEκ regulates κ rearrangement, we employed homologous recombination to mutate individual functional motifs within iEκ in the endogenous κ locus, including the NF-κB binding site (κB), as well as κE1, κE2, and κE3 E boxes. Analysis of the impacts of these mutations revealed that κE2 and to a lesser ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
76
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 29 publications
3
76
0
Order By: Relevance
“…The previous studies have demonstrated the functional importance of iEk and 39Ek enhancers in Igk rearrangement during B cell development in vivo (6,16,38). Targeted mutation of the E2A-binding motifs in iEk impairs Igk rearrangement (16), directly demonstrating the crucial functions of E2A and iEk in Igk rearrangement in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous studies have demonstrated the functional importance of iEk and 39Ek enhancers in Igk rearrangement during B cell development in vivo (6,16,38). Targeted mutation of the E2A-binding motifs in iEk impairs Igk rearrangement (16), directly demonstrating the crucial functions of E2A and iEk in Igk rearrangement in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Vk genes also contain E-boxes in their promoters and in close proximity to RSSs (12)(13)(14)(15). Moreover, targeted mutation of the E-boxes, E1 and E2, in iEk impairs Igk rearrangement (16), directly demonstrating the functional importance of E-proteins in Igk rearrangement during B cell development in vivo.…”
mentioning
confidence: 99%
“…Ig V(D)J gene rearrangement is controlled by STAT5, Pax5 and YY1, whereas IgL VJ gene rearrangement is regulated by the E2A proteins [10,19,20,21,22,23]. The E2A proteins interact directly with binding sites present in the IgK light chain gene enhancer to modulate IgK VJ gene rearrangement [24]. Furthermore, in the presence of self-reactivity they promote receptor editing [25].…”
Section: Developmental-specific Regulation Of Antigen Receptor Gene Amentioning
confidence: 99%
“…14 14 However, this particular kB-binding site was not essential for rearrangement in vivo. 15 This does not rule out a redundant role for this site nor does it exclude a contribution of NF-kB at other sites. The most notable experiment supporting a role for NF-kB in demethylation utilized v-Abl-transformed pre-B-like cells.…”
mentioning
confidence: 99%